Harmoni Falsafah Adat Basandi Syarak-Syarak Basandi Kitabullah, Kearifan Lokal Tungku Tigo Sajarangan dan Keberlanjutan Ekonomi di Ranah Minangkabau - Cahya, Bayu Tri; Maharany, Indah Dewi; Restuti, Dwi Putri (TSAQAFAH, 2025)
The philosophy of Adat Basandi Syara' - Syara' Basandi Kitabullah is the culmination of the interaction, integration, and affiliation of Minangkabau customs that have existed since the ancestors and Islam that emerged later. At the level of implementation, this concept can be used as a pattern to improve the welfare of the people by focusing on the local economy, which is still based on the philosophy of adat. This research aims to explore practical concepts to enhance the role of Tungku Tigo Sajarangan in the sustainability of the local economy based on customary philosophy. This research uses a qualitative and phenomenological approach. The results from this study indicate that the Convergence of Tungku Tigo Sajarangan Based on Indigenous Philosophy indicates three points: Emphasizes the common interest based on the Quran and Hadith, the synergy of the three forces of the Minangkabau leadership system, and the Democratic leadership style reflected in deliberation. Further results found that the Foundation of Local Wisdom in Economic Sustainability in West Sumatra by the local government tries to restrict big retailers' domination, Local wisdom brought by the local tribe (minang) human intelligence, and those conditions create a competitive rivalry.